METHODOLOGY FOR IMPROVING PHYSICAL TRAINING OF CADETS OF THE MINISTRY OF EMERGENCY SITUATIONS ACADEMY - Jumaqulov D.M.; Boymatov X.X.; Bollasov A.K. (Proximus Journal Publishing, 2024)
This article highlights the results of training conducted under a program aimed at improving the physical fitness of cadets of the Academy of the Ministry of Emergency Situations, and also outlines the results achieved as a result of the training
Keywords: Academy of the Ministry of Emergency; cadets; professional and physical training